A comparison of examination outcomes in the Part 1 of FC Rad Diag (SA) before and after 2012 - Sihlangu, Siphamandla Cedric (My University, 2021)
INTRODUCTION: The fourth industrial revolution brings with it many changes in the way we do things. The vast knowledge expectation in the field of Radiology places a spotlight on the radiology teaching and learning curricula in postgraduate programs. Teaching and learning among radiology registrars, and practitioners seeking continuing education credits is changing with advances in technology. The College of Radiologists (CR) of the Colleges of Medicine of South Africa (CMSA) in 2012 decided to allow candidates entry to the Part 1 examination from either within a formal registrar program or prior to entering such a program. This was a departure from the previous rules, which matched those of the Fellowship of the Royal College of Radiologists (FRCR). There is currently no data, which addresses the impact of this decision on the examination outcomes of candidates. AIM: This study aimed to compare the FC Rad Diag (SA) Part 1 examination outcomes five years prior to 2012, i.e. from 2007 to 2011 and five years after 2012, i.e. from 2012 to 2016. METHOD: This descriptive quantitative study describes the outcomes of the FC Rad Diag (SA) Part 1 from 2007 to 2016. A total number of 717 candidates took the exam during the study period. Descriptive statistics were used to describe the examination outcomes in the two periods under study (pre and post 2012). Inferential statistics were then applied to establish the relationship between the two periods. RESULTS: The mean pass rate from 2007 to 2011 and 2012 to 2016 were 54.6% (± 13.9%) and 44.8% (± 10.6%) respectively. The mean difference between the overall pass rates of the two time periods is 9.8% and is not significant (p = 0.0924). For the 2012 to 2016 period there was no significant difference in the mean pass rates of candidates not in formal training (34.6%) and the mean pass rates of all the candidates in formal training (44.8%), (p = 0.0828). CONCLUSION: This study revealed that candidate performance in the FC Rad Diag (SA) Part 1 is similar for candidates in University training posts to those candidates writing outside a formal training post
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Diagnostic Radiology, 2021